#ReclaimTheCity: the use of Facebook to engage the state and the public on affordable housing delivery in Cape Town, South Africa - Mshelia, Saratu (Department of Environmental and Geographical Science, 2025)
The global increase in the use of social media has enabled the real-time connection of people across localities, the fast sharing of information and the mobilisation of communities for a common cause. Social movements are increasingly leveraging this phenomenon to expand their activism to the digital space to reach a wider audience. This is true in the South African context as well where Reclaim the City (RTC) and Ndifuna Ukwazi (NU) – the two cases for this research – utilise a social media platform, namely, Facebook, to engage with the State and the public on affordable housing delivery in Cape Town. To understand how Facebook is utilised by these organisations, a qualitative research approach was adopted. First, a systematic review of posts published between 2017 and 2020 on the Facebook pages of RTC and NU was undertaken, excluding the contents of comments to the posts. Second, five semi-structured interviews – three with participants from RTC and two from NU – were also conducted. Lastly, non-participant observation was also undertaken at three events organised by the organisations to understand the link between their online and offline engagements. The findings indicate that RTC and NU have played significant roles in highlighting the need and urgency for affordable housing delivery in Cape Town's well-located areas. This has been achieved through in-person and online campaigns and activities. Focusing specifically on the digital realm, the findings indicate that Facebook serves as a complementary space of engagement for both RTC and NU. In this space, RTC shares personal stories on housing struggles and promotes its offline campaign events to raise public awareness and support. They also share information that provides insight into the State's obligations, promises and failures regarding affordable housing issues. NU, on the other hand, leverages its social media platforms to mostly educate the public on affordable housing delivery through the dissemination of housing research findings, providing information about tenancy rights and available support against eviction, as well as providing updates on state policies, projects and ongoing housing-related court cases. The findings illustrate that Facebook is an essential space for public sensitisation and mobilisation. However, as the findings further indicate, online campaigns are designed to support offline campaigns and in-person activities by mobilising the public. Yet, as the findings further indicate, the stated audience of RTC's Facebook page – the poor and working class – faces significant challenges in the form of high data costs which limit their engagement with the Facebook posts of RTC and NU. Thus, the findings intimate that social media serves as a complementary space of participation and primarily facilitates engagement with the upper working class and middle class.